The Wits Contemporary Performance Ensemble: a critical ethnography - Mullins, Angela Catherine (My University, 2010)
This research report explores the compositional identity South African composers, mostly born after 1976, are constructing. I conduct a critical ethnographic micro study of the Wits Contemporary Performance Ensemble (WCPE), a group of young composers and performers dedicated to workshopping and performing new compositions. South African compositional identity is explored and problematised in Chapter 1, along with the identification of two schools or types of composition within South Africa. The history and formation of the WCPE is discussed in Chapter 2, while the third chapter draws on interview data to present and problematise the field in which young composers work, discussing a series of perceived ‘lacks’ that affect their ability to produce new music. The fourth chapter critiques and evaluates the progress the WCPE made, using Timothy Rice’s model of the Subject-Centered Musical Ethnography (2003), to interpret what the music of these young composers is saying about the time and place in which they live. The conclusion considers the impact the WCPE has had on young South African composers and the necessity of a group like this in the formation of a new South African compositional voice.
MMus, Wits School of Arts, Faculty of Humanities, University of the Witwatersrand, 2009
Keywords: music composition; South African composers